Digital archive for high-end craftsmanship processes. Comparing research paths in Italy and China - Gabriele Goretti; Margherita Tufarelli; Qian Xiaobo (Agathón)
This article approaches the digitisation of the Intangible Heritage preserved by the traditional craft processes of SME manufacturing districts through a comparison of two case studies. Two distinct manufacturing areas – furniture and accessories in Tuscany (Italy) and Miao silverware in Guizhou Province (China) – are investigated in terms of their characteristics, structures and capacity to access technological innovation. The proposed analysis highlights on emerges a privileged role of the digital archive as a catalyst of creative and organisational processes. On the one hand, it favours the construction of an organised and transmissible memory that supports SMEs in their market competitiveness. On the other, it serves as a basis for developing user-experience processes aimed at dissemination and reintegration in the context of contemporary design.